A 36-Pulse Diode Rectifier with an Unconventional Interphase Reactor - Yuxin Lian; Shiyan Yang; Hongqi Ben; Wei Yang (Energies, 2019)
This paper proposes a simple 36-pulse diode rectifier with an unconventional interphase reactor (IPR) and single-phase full-wave rectifier (SFR). The primary winding of the unconventional IPR is double tapped and the secondary winding is connected with SFR. The operation mode of the unconventional IPR is analyzed, and the optimal tap ratio and turn ratio of the unconventional IPR are designed from both viewpoints of input line current and load voltage. With the optimal parameters of the unconventional IPR, the proposed rectifier extends the conventional 24-pulse rectifier operation to 36-pulse operation and draws near sinusoidal input line currents, the total harmonic distortion (THD) of which is about 5.035%. The kVA rating of the unconventional IPR is about 2.6% of the output power. Compared with the conventional 36-pulse rectifier with triple-tapped IPR, the proposed 36-pulse rectifier is easy and simple to implement instead of using control circuits. Experiment results are provided to verify the theoretical analysis.